Impact of the COVID-19 pandemic on the codification of China’s civil code - Zhai, Gaoyuan; Liu, Xiaochang (Frontiers in Public Health, 2024)
The COVID-19 pandemic has spread widely around the world since 2019, wreaking havoc on social order in a global context. In China, the pandemic has not only provided new challenges to the government’s capacity but also provided new issues for the Civil Code that is being compiled. The study adopts the research method of comparative analysis and combines the case study method, aiming to study the impact of the epidemic on the compilation of China’s Civil Code. We found that the official Civil Code adds, deletes, and adjusts several articles compared to the Civil Code (Draft), five of which are relevant to the COVID-19 pandemic. The Civil Code was enacted at the time of the COVID-19 pandemic, which led to some of its provisions being affected by the COVID-19; the “COVID-19 provisions” not only provided legitimacy for the prevention and control of the pandemic but also improved China’s system of governance of public health emergencies. This study exposes the legal loophole in the “COVID-19 provisions” in China’s Civil Code and further suggests ways to fill the legal loophole.